Metal-hydride hydrogen atom transfer (MHAT) reactions in natural product synthesis - Wu, Jinghua; Ma, Zhiqiang (Organic chemistry frontiers an international journal of organic chemistry, 2021)
The metal-hydride hydrogen atom transfer (MHAT) reaction plays an important role in the field of natural product synthesis. MHAT, as a powerful method, has been employed by chemists to construct C–C, C–H, and C–heteroatom bonds. In this review, we summarize the recent total synthesis of natural products using MHAT to functionalize olefins with first-row transition metal catalysts such as cobalt, manganese and iron.